Adipose tissue-derived human mesenchymal stromal cells can better suppress complement lysis, engraft and inhibit acute graft-versus-host disease in mice - Stanley Chun Ming Wu; Manyu Zhu; Stanley C. C. Chik; Maxwell Kwok; Asif Javed; Laalaa Law; Shing Chan; Kenneth R. Boheler; Yin Ping Liu; Godfrey Chi Fung Chan; Ellen Ngar-Yun Poon (Stem Cell Research & Therapy, 2023)
Abstract Background Acute graft-versus-host disease (aGvHD) is a life-threatening complication of allogeneic hematopoietic stem cell transplantation (HSCT). Transplantation of immunosuppressive human mesenchymal stromal cells (hMSCs) can protect against aGvHD post-HSCT; however, their efficacy is limited by poor engraftment and survival. Moreover, infused MSCs can be damaged by activated complement, yet strategies to minimise complement injury of hMSCs and improve their survival are limited. Methods Human MSCs were derived from bone marrow (BM), adipose tissue (AT) and umbilical cord (UC). In vitro immunomodulatory potential was determined by co-culture experiments between hMSCs and immune cells implicated in aGvHD disease progression. BM-, AT- and UC-hMSCs were tested for their abilities to protect aGvHD in a mouse model of this disease. Survival and clinical symptoms were monitored, and target tissues of aGvHD were examined by histopathology and qPCR. Transplanted cell survival was evaluated by cell tracing and by qPCR. The transcriptome of BM-, AT- and UC-hMSCs was profiled by RNA-sequencing. Focused experiments were performed to compare the expression of complement inhibitors and the abilities of hMSCs to resist complement lysis. Results Human MSCs derived from three tissues divergently protected against aGvHD in vivo. AT-hMSCs preferentially suppressed complement in vitro and in vivo, resisted complement lysis and survived better after transplantation when compared to BM- and UC-hMSCs. AT-hMSCs also prolonged survival and improved the symptoms and pathological features of aGvHD. We found that complement-decay accelerating factor (CD55), an inhibitor of complement, is elevated in AT-hMSCs and contributed to reduced complement activation. We further report that atorvastatin and erlotinib could upregulate CD55 and suppress complement in all three types of hMSCs. Conclusion CD55, by suppressing complement, contributes to the improved protection of AT-hMSCs against aGvHD. The use of AT-hMSCs or the upregulation of CD55 by small molecules thus represents promising new strategies to promote hMSC survival to improve the efficacy of transplantation therapy. As complement injury is a barrier to all types of hMSC therapy, our findings are of broad significance to enhance the use of hMSCs for the treatment of a wide range of disorders.